(untitled) - Ferrara, Cosmo F. (New York,US, 1989)
This book is divided into six chapters. Chapter one explains the concept of rhrtoric, gives an overview of the writing process, and discusses how a writer makes choices about subtance structure,...
Keywords: Readers,English language,Academic writing,Rhetoric,Biện pháp tu từ,Văn chính luận,Ngôn ngữ tiếng Anh,Độc giả; Rhetoric,Study and teaching.,History,Lịch sử,Dạy và học,Biện pháp tu từ